Search found 2 matches

Author Message
Vikash_Pradhan
Replies:
6
Views:
884
Thanks:
0

help neeeded plsss!!!

Forum:
Problem Solving
Posted:
Wed Mar 14, 2012 1:27 am
Considering the equation in the form:
A d^2 + B d + C = 0

My Equation:
15 d^2 + d(12 - 5 e) - (49 + 4 e) = 0
A = 15
B = (12 - 5 e)
C = - (49 + 4 e)

Your Equation:
15 d^2 + (5 e - 12) d ...
Vikash_Pradhan
Replies:
6
Views:
884
Thanks:
0

help neeeded plsss!!!

Forum:
Problem Solving
Posted:
Tue Mar 13, 2012 6:31 am
The Quadratic equation seems dubious to me.

3d - 7^2 / (4+5d) = e (multiply both sides with 4 + 5 d)
3d (4 + 5 d) - 49 = e (4 + 5 d) {open the brackets}
Then:

12 d + 15 d^2 - 49 = 4 e + 5 ...
  • New posts
  • New posts [ Popular ]
  • New posts [ Locked ]
  • No new posts
  • No new posts [ Popular ]
  • No new posts [ Locked ]
  • Announcement
  • Sticky